An analytical study of foreign direct investment in Algeria for the period (2001-2020) - Slimane, Nessah; Ilyas, Laidani; Djillali, Bouzekri; Aissa, Smail; Fatma, Rebhi (International journal of economic perspectives, 2025)
The importance of foreign direct investment and its repercussions on host and investor countries prompted us to present this research paper, presenting an analytical study of foreign direct investment in Algeria and what the state sought to adapt its economy in line with the market economy, and this through studying the case of Algeria from 2001 to 2020 and the extent of the development of foreign investment in Algeria. The study concluded that the result of the evaluation of investment climate indicators in Algeria by international bodies was negative and did not meet the expectations of investors, represented in the economic freedom index, the transparency index and the global competitiveness index, in addition to the global competitiveness index.